The Death of Character in Postdramatic Comedy - Jure Gantar (Amfiteater, 2022)
According to Elinor Fuchs, the main characteristic of postmodern theatre and, consequently, the main reason for the decline of the dramatic text as the most important element of classical theatre is the death of character. While the traditional Hegelian view of drama depends heavily on a unified fictional subject, Fuchs argues that both modern and postmodern theatre destabilise and subvert this subject to the degree that we can no longer see it as a coherent whole. Yet, her theory, like Hans-Thies Lehmann’s, has one notable methodological weakness: she almost entirely ignores comedy. Her study omits in its analysis a substantial portion of the repertoire not only of the mainstream but also of fringe and experimental theatres. This paper attempts to rectify this omission and hopes to determine whether character also disappears from postdramatic comedy and not just from serious postdramatic theatre. The analysis focuses on three forms of postmodern comedy that deviate from the traditional narrative format and seem to support Fuchs’s reading: on sketch, stand-up and improvisational comedy. Using examples from sketch comedy Beyond the Fringe, George Carlin’s stand-up acts and The Second City improvs, the main body of the argument tests the cogency of the basic tenets of Fuchs’s theory. The second part of the paper offers a counterargument and a possible supplement to her hypothesis.